Recent advances in sterilization and disinfection technology: A review. (December 2022) - Bharti, Bandna; Li, Hanliang; Ren, Zhaoyong; Zhu, Rongshu; Zhu, Zhenye
Abstract: Sterilization and disinfection of pollutants and microorganisms have been extensively studied in order to address the problem of environmental contamination, which is a crucial issue for public health and economics. Various form of hazardous materials/pollutants including microorganisms and harmful gases are released into the environment that enter into the human body either through inhalation, adsorption or ingestion. The human death rate rises due to various respiratory ailments, strokes, lung cancer, and heart disorders related with these pollutants. Hence, it is essential to control the environmental pollution by applying economical and effective sterilization and disinfections techniques to save life. In general, numerous forms of traditional physical and chemical sterilization and disinfection treatments, such as dry and moist heat, radiation, filtration, ethylene oxide, ozone, hydrogen peroxide, etc. are known along with advanced techniques. In this review we summarized both advanced and conventional techniques of sterilization and disinfection along with their uses and mode of action. This review gives the knowledge about the advantages, disadvantages of both the methods comparatively. Despite, the effective solution given by the advanced sterilization and disinfection technology, joint technologies of sterilization and disinfection has proven to be more effective innovation to protect the indoor and outdoor environments. Graphical abstract: Image 1 Highlights: Conventional sterilization/disinfection techniques were discussed. To address advanced technologies of sterilization and disinfection. The advanced technology can replace conventional techniques and reach the unmet needs. Joint technologies show the better efficiency compared to the alone techniques.